From legalism to value-oriented Islamic finance practices. Issue 4 (14th November 2016) - Bin Hasan, Zulkifli
Abstract : Purpose: This paper aims to provide analysis on the state of Islamic finance through critical appraisal on its current form and practices. This paper argues that the current form of Islamic finance practices is due to its legalistic approach and hence requires value-oriented reform. In this regard, Shari'ah governance system can be one of the mechanisms toward such reformation. Design/methodology/approach: This paper uses case study research method and comparative studies of other's works to develop understanding on the extent of Islamic finance practices. The study utilizes descriptive, comparative and critical analysis approaches in extracting and analyzing the information. Findings: The literature has indicated the growing frustration of scholars and proponents of Islamic economics on the failure of Islamic finance in addressing the real economic and ethical issues beyond the legal realm of Shari'ah compliance. Legalism leads to a narrow understanding and ignores certain dimensions of Islamic finance practices. Considering all factors and through critical observation, this paper argues that the current form of Islamic finance practices is due to its legalistic approach and hence requires value-oriented reform. At this juncture, the paper suggests that Shari'ah governance system can be one of the mechanisms toward such reformation. Originality/value: This paper provides valuable discussion and fresh and recent information on Islamic finance practices, including Shari'ah governance practices of Islamic financial institutions (IFIs) through case studies. The study shares experience of Malaysia in developing its Islamic finance framework and practices from legalistic toward value-oriented approach.